“Los factores externos: la salud en el aprendizaje” - Tanguila Vaca, Gabriela Estefania (2022)
Education is a social process that prioritizes the formation of an individual through experiences throughout his life, to form beings capable of making their own decisions and integrate into society, for this reason, the teaching-learning process is a space where the teacher lives daily with the student, knows the strengths and weaknesses that each of them present. In this sense, the objective of the research was to identify the external factors in relation to health through a life history for the understanding of the learning process in sixth grade students of the Educational Unit "San José de Guaytacama" of the Province of Cotopaxi, Canton Latacunga, Guaytacama Parish. The methodology applied is qualitative because it consists of the collection of data from the description of the innate characteristics of the participants of the research; through the interview technique that was executed to collect information from a student, parent and teacher. When carrying out the life history it was evidenced that the student does not have adequate nutrition, which causes sleepiness in the first hours of class, thus preventing correct learning.The proposal was the construction of a life history, with the purpose of understanding the characteristics, facts or reasons of the external factors: health in learning and how they affect the educational quality, from this, a workshop was elaborated with the name "I want to be your hero" which consists of activities that favor the links between the family. As for the results, it was identified that the proposed activities helped to strengthen the affective development and parents through knowledge of nutrition, grooming habits and well-being with mental health. Therefore, this research helped parents and students to recognize the importance of good health, pedagogical and emotional support.